Ameloblastic carcinoma: a clinicopathologic analysis of cases seen in a Nigerian Teaching Hospital and review of literature - Soyele, Olujide Oladele (Pan Afr Med J, 2018)
INTRODUCTION: Ameloblastic carcinoma is a rare malignant odontogenic neoplasm that exhibits histological features of ameloblastoma in combination with cytological atypia. It may arise de novo or secondarily through malignant de-differentiation of pre-existing ameloblastoma or odontogenic cyst. Secondary ameloblastic carcinomas often results from repeated surgical intervention, which is a mainstay of odontogenic tumor management in resource limited settings. To date, relatively few cases of ameloblastic carcinomas have been reported and many cases have been misdiagnosed as ameloblastoma. This is due to its wide range of clinicopathological feature which range from indolent to aggressive. It may present as an aggressive ulcerated mass or as a simple cystic lesion; hence, it often challenging to delineate from its benign counterpart, ameloblastoma. METHODS: this study reviewed the clinicopathological data on 157 cases of odontogenic tumors diagnosed over a 10 years period from the pathology archive of the Oral Pathology Unit of Obafemi Awolowo University Teaching Hospital Complex (OAUTHC), Ile-Ife, Nigeria. RESULTS: of all these cases, we identified that 64.9% were Ameloblastomas, while 8.3% were ameloblastic carcinomas. Primary subtypes of ameloblastic carcinoma constituted 23.08%, while 69.23% of the cases were of the secondary subtype. We also found that the secondary subtype of ameloblastic carcinomas showed a higher mean duration value of 7.7 years. Most lesions were found in posterior mandible and presented with ulceration, perforation and ill-defined borders radiographically. CONCLUSION: this study is among the few that have documented higher frequency of secondary ameloblastic carcinoma in the scientific literature.